A recyclable carbon nanoparticle-based fluorescent probe for highly selective and sensitive detection of mercapto biomolecules. Issue 1 (6th November 2014) - Lan, Minhuan; Zhang, Jinfeng; Chui, Ying-San; Wang, Hui; Yang, Qingdan; Zhu, Xiaoyue; Wei, Huaixin; Liu, Weimin; Ge, Jiechao; Wang, Pengfei; Chen, Xianfeng; Lee, Chun-Sing; et al.
Abstract : Hg 2+ quenched CNPs (CNP-Hg 2+ ) as a highly sensitive and selective reversible probe for the detection of mercapto biomolecules in aqueous solutions and in living cells. Abstract : Carbon nanoparticles (CNPs) with strong blue emission are synthesized using a microwave-assisted hydrothermal method. The fluorescence of the CNPs can be completely quenched by Hg 2+ through an effective electron or energy transfer process due to the synergetic strong electrostatic interaction and metal–ligand coordination. Based on this, a system containing Hg 2+ -quenched CNPs (CNP-Hg 2+ ) is designed to be a sensitive and selective turn-on fluorescent probe towards cysteine (a type of mercapto biomolecule) with a detection limit of 15 nM. The fluorescence of CNP-Hg 2+ aqueous solution can be repeatedly turned on and off for over 10 times by alternative addition of cysteine and Hg 2+, respectively. After 10 cycles, the fluorescence intensity could be recovered to as high as 85% of the original value of CNPs. Remarkably, the sensing process is able to be observed by the naked eye under UV irradiation. Furthermore, the sensing is specific to biothiols and the sensor is able to work in living cells.